Effect of steam to carbon ratio (S:C) on steam methane reforming’s yield over coated nickel aluminide (Ni3Al) catalyst in micro reactor - Rais Hanizam Madon,; Mas Fawzi,; Khairul Ilman Sarwani,; Shahrul Azmir Osman,; Mohd Azahari Razali,; Abdul Wahab Mohammad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This work looks into the effect of Steam to Carbon ratio (S:C) on methane (CH4 ) conversion and hydrogen (H2 ) yield over coated Nickel Aluminide (Ni3 Al) catalyst in micro reactor. The Ni3 Al is an intermetallic alloy which known to have good catalytic activity and selectivity. The Ni3 Al catalyst precursor was prepared through dip coating technique at 10wt% on top of substrate plate and characterized by X-Ray Diffraction (XRD), Scanning Electron Microscope-Energy Dispersive X-Ray Spectroscopy (SEM-EDX), Temperature Programming Reduction (TPR), activated by H2 reduction, and catalytic activity test in steam methane reforming (SMR) reaction in micro reactor at S:C 2, S:C 3 and S:C 4 with 650°C reaction temperature and 300 minutes reaction time. The characterization showed the presence of Ni3 Al on top of the coating surface and successfully been activated at 500°C and 46 minutes. The CH4 conversion and H2 yield in the product of the reaction were quantified using the Gas Chromatograph technique. From the series of experiments, it was found that S:C 4 produced the highest methane conversion of 65.56% and S:C 3 produced the highest hydrogen yield of 41.34%. The S:C 2, showed faster and smoother stability trend conversion as early as 180 minutes from the start of the reaction. However, S:C 3 showed the most optimum methane conversion and hydrogen yield and achieved stability trend conversion within the defined reaction time range of 300 minutes. It is inferred that the S:C 3 is the best steam to carbon ratio for the developed catalyst in these settings.